2020
DOI: 10.1016/j.brat.2020.103638
|View full text |Cite
|
Sign up to set email alerts
|

Changing the future: An initial test of Future Specificity Training (FeST)

Abstract: A range of psychiatric disorders are characterised by impairments in episodic future thinking (EFT), and particularly simulating specific, spatiotemporally-located future events. No study has examined whether training can lead to sustained improvement in specific EFT. In this study, participants (N = 60; M age = 31, SD = 13.2) were randomized to a two-session, group-based future thinking program (Future Specificity Training; FeST) or wait-list. At follow-up the training group, relative to wait-list, showed lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 55 publications
2
30
0
Order By: Relevance
“…Further testing to establish these selective effects in clinical groups is needed though. The findings are also relevant for interventions focused on improving autobiographical thinking, such as Future Specificity Training (FeST; Hallford, Yeow et al, 2020). Incorporating elaboration on spatial details in these programs might improve the effects on outcomes such as use of detail/vividness and perceived control.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Further testing to establish these selective effects in clinical groups is needed though. The findings are also relevant for interventions focused on improving autobiographical thinking, such as Future Specificity Training (FeST; Hallford, Yeow et al, 2020). Incorporating elaboration on spatial details in these programs might improve the effects on outcomes such as use of detail/vividness and perceived control.…”
Section: Discussionmentioning
confidence: 91%
“…Previous research has indicated that detail and vividness is associated with more use of mental imagery (Hallford, Farrell, & Lynch, 2020), and that both vividness and mental imagery are related to higher anticipatory and anticipated pleasure (Hallford, Barry et al, 2020), a stronger sense of perceived control (Jing, Madore, & Schacter, 2106) and a higher perceived likelihood of for positively-valenced future events (Boland et al, 2018). Trials in clinical groups (Hallford, Sharma, & Austin, 2020) and non-clinical groups (Hallford, Yeow et al, 2020) have already shown that training in enhancing detail and specificity in future thinking can influence such processes. Distinguishing the effects of particular types of details would provide a more nuanced understanding of their benefit in functioning.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Some examples come from the context of depression, in which a difficulty imagining positive future events has been linked to symptoms such as anhedonia and lack of motivation. Approaches have included practice in generating vivid and specific imagery of future events (Hallford et al 2020b;Hallford et al 2020c) or rewarding experiences (Linke and Wessa 2017), or computerised cognitive training approaches involving repeated generation of positive imagery (e.g. Blackwell et al 2015;Dainer-Best et al 2018).…”
Section: Dysfunctional Mental Imagerymentioning
confidence: 99%
“….003 details and vividness of the narratives, making it hard to distinguish between these two components. Moreover, only positive events were investigated in Hallford et al (2020c), since it has been found that deficits in detail/vividness may be specific to positive events in depression (Holmes et al 2016). As participants were not requested to only evoke positive events in the current study, further investigations are needed to explore the potential role of events' valence on vividness.…”
Section: Eft and Associations With Ap And Sfmentioning
confidence: 99%